Eficácia do uso de plasma em pressão atmosférica na adesão de cerâmicas zircônia - Lilian Capanema Nogueira (2018)
Efficacy of the use of plasma at atmospheric pressure in zirconia adhesion One of the major challenges today in the science of dental materials is the achievement of effective and durable bonding to ceramics with high crystalline content. The objective of the present study was to evaluate the efficacy of plasma at atmospheric pressure in the adhesion of ceramic zirconia through the bond strength, surface energy and type of fracture of two ceramic systems after different forms of surface treatment associated with the application of plasma at atmospheric pressure. For the study forty zirconia plates (12 mm x 5 mm x 1.5 mm) were obtained from two zirconia ceramics (E.max ZirCad and Calypso), polished and cleaned by ultrasound for 5 minutes. Randomly divided into 2 groups according to the ceramic system and 4 subgroups (n = 5) according to the surface treatment, control (primer), primer + blasting with micrometric alumina (Al2O3) particles, primer + blasting with micrometric particles of alumina (Al2O3) + plasma, primer + plasma. One hundred and twenty cylinders of composite resin (Z-100) were made using cylindrical matrices (1.0 mm x 3.0 mm) cemented on the zirconia plates. The specimens were stored in distilled water for 24 hours at 37°C, then tested for microshear on a Shimadzu EZ test machine at 0.5 mm / min. The obtained data were submitted to statistical analysis for comparison between the E.max and Calypso groups in relation to the bond strength (strength / area - Mpa), contact angle and fracture types. The data were analyzed by ANOVA One-Way and Kruskal-Wallis tests for bond strength (p=0.003) and (p=0.005) and contact angle (p<0.001) and (p<0.001). There was no significant difference for the fracture data (p = 0.145), by the chi-square test, with a predominance of mixed fractures. The bond strength values of the Y-TZP ceramics showed higher values when the plasma was associated with blasting with aluminum oxide and / or primer and the application of only the plasma did not exceed the values reached by the other forms of surface treatment. This association resulted in lower values of contact angles. It is a higher frequency of mixed fractures when only aluminum oxide treatment is performed and when it is associated with plasma.